1996
DOI: 10.1063/1.471021
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy, polarization and nonadiabatic dynamics of electronically excited Ba(Ar)n clusters: Theory and experiment

Abstract: Molecular Dynamics simulations using a surface-hopping method for transitions between different electronic states are employed to study the dynamics following photoexcitation of the Ba(Ar) 125 cluster. The results are used to interpret spectroscopic experiments on large, size-distributed Ba(Ar) n clusters. The dynamics of the coupled electronic-nuclear motions in the cluster involves transitions between three potential energy surfaces, corresponding to the nearly-degenerate p-states of the excited Ba atom. Eje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Contrary to Ba 12,21 or Ca 14 on an Ar surface, for which the ejection of the metal atom is a minor process, it occurs systematically for excitation of potassium in this energy range.…”
Section: Relaxation Dynamics Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…Contrary to Ba 12,21 or Ca 14 on an Ar surface, for which the ejection of the metal atom is a minor process, it occurs systematically for excitation of potassium in this energy range.…”
Section: Relaxation Dynamics Analysismentioning
confidence: 86%
“…In both cases, the P manifold near the surface of an argon cluster results in two bonding Π-like states and one Σ-like state. However, the Σ state is associative for alkaline earth metals 12,14 whereas it is 15 9.9/90.9 9.04/117 dissociative in the case of potassium, as we shall see in this paper. This difference reflects the relative difference of the spatial extension of the atomic p orbitals between these two kinds of atoms.…”
Section: Introductionmentioning
confidence: 87%
“…The TSH method requires the diagonalization of the Hamiltonian matrix at each time step in order to determine the adiabatic states "on the fly" while no diagonalization is involved in the HWD method. This fact is not crucial when only few states are involved, as in the recent study [28] of Ba(Ar) n where only the three electronic states of the barium atom are involved in the dynamics. However for larger Hamiltonian matrices the TSH method may become prohibitive since the computer time for the diagonalization grows as N 3 .…”
Section: Dissociationmentioning
confidence: 92%
“…Excitation of BaAr N into the ⌺-like state is followed by a fast relaxation into the ⌸-like state as evident from a single broad band observed in the BaAr N fluorescence spectra. 8,9 Indeed the molecular dynamics simulations of Krylov et al 27 have shown this ⌺Ϫ⌸ relaxation to be complete within about 10 ps. This rate of relaxation is evidently much more rapid than that of the barium deactivation by both argon and methane.…”
Section: A Mechanism For the Ba( 1 P 1 ) Deactivationmentioning
confidence: 97%
“…In fact a recent molecular dynamics simulation of electronically excited state BaAr N clusters has shown that this relaxation time is of the order of 10 ps. 27 However, excitation of the ⌺-like branch with a sufficiently high energy leads to the appearance of the atomic Ba( 1 S 0 Ϫ 1 P 1 ) line in the emission spectra. 8,9 This is a direct observation of the competition that exists between energy disposal into a Ba-Ar dissociation coordinate, whereupon the barium is desorbed resulting in the resonance line, and energy disposal in the cluster which acts as a thermal bath, giving rise to the broad emission.…”
Section: Introductionmentioning
confidence: 99%